Late-stage diversification of bacterial natural products through biocatalysis - Lazic, Jelena; Filipovic, Vuk; Pantelic, Lena; Milovanovic, Jelena; Vojnovic, Sandra; Nikodinovic-Runic, Jasmina (Frontiers in Bioengineering and Biotechnology, 2024)
Bacterial natural products (BNPs) are very important sources of leads for drug development and chemical novelty. The possibility to perform late-stage diversification of BNPs using biocatalysis is an attractive alternative route other than total chemical synthesis or metal complexation reactions. Although biocatalysis is gaining popularity as a green chemistry methodology, a vast majority of orphan sequenced genomic data related to metabolic pathways for BNP biosynthesis and its tailoring enzymes are underexplored. In this review, we report a systematic overview of biotransformations of 21 molecules, which include derivatization by halogenation, esterification, reduction, oxidation, alkylation and nitration reactions, as well as degradation products as their sub-derivatives. These BNPs were grouped based on their biological activities into antibacterial (5), antifungal (5), anticancer (5), immunosuppressive (2) and quorum sensing modulating (4) compounds. This study summarized 73 derivatives and 16 degradation sub-derivatives originating from 12 BNPs. The highest number of biocatalytic reactions was observed for drugs that are already in clinical use: 28 reactions for the antibacterial drug vancomycin, followed by 18 reactions reported for the immunosuppressive drug rapamycin. The most common biocatalysts include oxidoreductases, transferases, lipases, isomerases and haloperoxidases. This review highlights biocatalytic routes for the late-stage diversification reactions of BNPs, which potentially help to recognize the structural optimizations of bioactive scaffolds for the generation of new biomolecules, eventually leading to drug development.